Effect of fluoridated varnish and silver diamine fluoride on enamel demineralization resistance in primary dentition - Najmeh Mohammadi; Mohammad Hossein Farahmand Far (Wolters Kluwer Medknow Publications, 2018)
Background: International data on caries epidemiology confirm that dental caries remains a significant disease of childhood in both developing and developed countries. Based on preventive dentistry, topical fluoride may be a useful measure to arrest caries lesions. Fluoride used in various forms have been proven to be effective in dental caries prevention. Aim: This study aims to compare the effect of fluoridated varnish and silver diamine fluoride (SDF) solution on primary teeth enamel resistance to demineralization. Methods: Forty-five caries-free deciduous canine teeth extracted due to orthodontic reasons, devoid of any defects were selected. Teeth were mounted on acrylic blocks as their buccal surface was exposed and baseline surface microhardness (SMH) determination was accomplished. Enamel samples were randomly distributed into three groups with 15 specimens each. One group was used as control (distilled and deionized water) (C); in the other groups, either a fluoridated varnish (V) or an SDF solution was applied to the enamel blocks. The blocks of each group were submitted to pH-cycling solutions and treatment regimen. After pH-cycling process, SMH determination was done again for all samples. Results: According to the present findings, the percentage of decrease in SMH of control group is numerically greater than other groups and also SDF group shows the most resistance against mineral loss. However, based on one-way ANOVA test, this difference is not statistically significant (P = 0.217). Conclusion: SDF solution and fluoride varnish display similar effectiveness in preventing the demineralization of deciduous anterior teeth, and no significant difference was observed.